Solution Studies on DNA Interactions of Substitution-inert Platinum Complexes mediated via The Phosphate Clamp - Qu, Y. (Dalton Trans, 2015)
The phosphate clamp is a distinct mode of ligand-DNA binding where the molecular is manifest through (“non-covalent”) hydrogen-bonding from am(m)ines of polynuclear platinum complexes to the phosphate oxygens on the oligonucleotide backbone. This third mode of DNA is unique from the “classical” DNA intercalators and minor groove binding agents and even the closely related covalently binding mononuclear and polynuclear drugs. 2D (1)H NMR studies on the Dickerson Drew Dodecamer (DDD, d(CGCGAATTCGCG)(2)) showed significant A-T contacts mainly on nucleotides A6, T7 and T8 implying a selective bridging from C9G10 in the 3' direction to C9G10 of the opposite strand. {(1)H, (15)N} HSQC NMR Spectroscopy using the fully (15)N-labelled compound ([{trans-Pt(NH(2))(3)(H(2)N(CH(2))(6)NH(3)}(2)μ-(H(2)N(CH(2))(6)NH(2))(2)(Pt(NH(3))(2)](8+) (TriplatinNC) showed at pH6 significant chemical shift and (1)J((195)Pt-(15)N) coupling constants from free drug and DDD-TriplatinNC at pH 7 indicative of formation of the phosphate clamp. (31)P NMR results are also reported for the hexamer d(CGTACG)(2) showing changes in (31)P NMR chemical shifts indicative of changes around the phosphorous center. The studies confirm the DNA binding modes by substitution-inert (non-covalent) polynuclear platinum complexes and help to further establish the chemotype as a new class of potential anti-tumor agents in their own right with a distinct profile of biological activity.